Interpreting and living God's law at Qumran: Miqṣat Maʿaśe Ha-Torah, some of the works of the Torah (4QMMT) : introduction, text, translation and interpretative essays - Kratz, Reinhard Gregor (SAPERE, 2020)
Cover -- Title -- Sapere -- Preface to this Volume -- Table of Contents -- A. Introduction -- Introduction (Reinhard G. Kratz) -- 1. The Dead Sea Scrolls and the Community of Qumran -- 1.1. The Findings -- 1.2. The Problem of Historical Contextualization -- 1.3. The Witness of the Texts -- 1.4. The Historical Context -- 2. Miqṣat Ma‛aśe Ha-Torah, "Some of the Works of the Torah" (4QMMT) -- 2.1. The Content -- 2.2. The Manuscripts -- 2.3. Editions and Research -- 2.4. This Volume -- B. Text, Translation and Notes -- Miqṣat Ma‛aśe Ha-Torah, Some of the Works of the Torah (Text, Translation and Notes by Reinhard G. Kratz) -- C. Essays -- Material Construction and Palaeographic Dating of 4QMMT: The Evidence of the Manuscripts (Eibert Tigchelaar) -- 1. Material construction in the Qimron / Strugnell edition -- 2. Alternative material constructions relating to 4Q398 11-13 -- 3. Previous palaeographic analyses of the MMT manuscripts -- 4. Palaeographical comments relating to individual manuscripts -- 5. Preliminary palaeographical conclusions -- The Language of 4QMMT (Noam Mizrahi) -- 1. Background -- 2. MMT -- 3. Lexicon (including semantics and phraseology) -- 4. Grammar -- 4.1. Morphology -- 4.2. Phonology -- 5. Syntax -- 6. Discursive and Text-Linguistic Aspects -- 7. Conclusion -- Law and Narrative: 4QMMT and the Hebrew Bible (Reinhard G. Kratz) -- 1. The literary unity of 4QMMT -- 2. Biblical quotations and allusions in 4QMMT B -- 3. Biblical quotations and allusions in 4QMMT C -- 4. The Relationship between 4QMMT B and C -- 5. Law and Narrative in 4QMMT and in the Jewish Tradition -- The Calendar and 4QMMT (Jonathan Ben-Dov) -- 1. Introduction -- 2. The kind of calendar contained in 4Q327 and 4Q394 -- 3. Are 4Q327 and 4Q394 the same scroll? -- 4. Is the Calendar of 4Q394 part of MMT? -- 5. Conclusion.